Perbaikan Kuliatas Arang Briket Menggunakan Metode Six Sigma Dan Triz - Alfin Arif Rochim; Ari Zaqi Al Faritsy (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
CV Harico is a manufacturing company that produces briquetted charcoal final products. In this research, the company had problems with the quality of charcoal briquettes which did not meet standards, amounting to 12% of the production process, including slanted shapes, holes and cracks. In this research, problem solving is done by combining the Six Sigma and TRIZ methods to get suggestions for improvement. The Six Sigma method is an organized and systematic method, Six Sgma has 5 stages, which can be known as the DMAIC phase. Based on the calculation of the DPMO value and the calculation of the sigma value at the measurement stage, the average DPMO value for October 2023-November 2023 was 27219 with a sigma value of 3.43. Based on the identification results using the Fishbone Diagram method and the FMEA method, the largest defects were found in the slanted shape of the charcoal briquettes, these results were obtained from the factor with the highest RPN value that caused defects. Proposed improvements based on the TRIZ method analysis include providing training, carrying out periodic actions, making maintenance schedules, evaluating work processes, changing tools to reduce the occurrence of defects. The aim of this research is to analyze the problems that occur as well as efforts to control quality and reduce product defects in briquetted charcoal products.